Flerstemmig gudstjeneste: Postkoloniale perspektiver på liturgi (Nordic Journal of Practical Theology, 2020)
While post-colonial theory for years has been well established in many academic disciplines, including theology and biblical studies, it has only recently begun to make its influence on liturgical practice and reflection. This article surveys areas explored in postcolonial liturgical thinking, such as activistic approaches to liturgy, critique of linear constructions of tradition, and a dominantly text-focused approach to liturgy, as well as attempting to develop a “postcolonial ear” for listening to the many voices and sounds from the margins of the liturgical canon. In conclusion, the author suggests possibilities of postcolonial perspectives in a Norwegian context.